(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study explores new designs of linear generators intended for wave energy conversion systems based on transverse magnetic flux machines (TFM) with permanent magnets. The main focus is on developing new, highly efficient designs of linear generators for wave energy, operating at low speeds. The developed wave energy converters function as direct-drive machines, where the generator’s translator is directly connected to the buoy. The working element performs a reciprocating motion, converting wave energy into mechanical energy, which is then transferred to the generator. As a result, the multi-pole TFM generator demonstrates high energy conversion efficiency even at low speeds. This eliminates the need for complex and unreliable hydraulic systems with compressors, simplifying the wave energy conversion system’s design and improving its overall reliability. Based on previous research on cylindrical transverse magnetic flux machines with a disk structure, conducted in close collaboration with Germany’s Otto-von-Guericke University, a theoretical analysis was performed and successfully validated through laboratory experiments. The experimental data confirmed the efficiency of the proposed generator concept. The findings from previous research were applied to linear types of electric machines, which were proposed and improved in the current study for use in wave energy conversion systems. One of the key achievements of this study was the introduction of a generator design that replaced the I-shaped core (the stator magnetic shunt) with an additional E-shaped core. This allowed the use of a double translator, located both inside and outside the stator core. This double translator and stator core design makes the generator more compact and increases the machine’s power. The study also determined the optimal number, size and shape of stator cores to achieve the best magnetic field saturation, which further increased the generator’s specific power. As a result, a new, promising design for a three-phase linear direct-drive generator with a nominal power of 2.3 kW and a translator speed of 1 m/s was designed. The generator’s magnetic system has an outer diameter of 220 mm and a stator core length of 1 meter. At this translator speed, the system efficiency reached approximately 80%, which is a significant improvement compared to traditional high-speed hydraulic systems. The study’s results also confirmed the scalability of the proposed generator design for use in high-power wave energy conversion systems. Such systems can be decentralized and operate in parallel along the shoreline, creating a network for converting ocean wave energy. Moreover, this research significantly contributes to the development of sustainable energy systems, offering an efficient, scalable, and innovative approach to harnessing wave energy. The new linear direct-drive generator designs not only reduce energy conversion losses compared to high-speed hydraulic indirect-drive systems but also promote decentralized production and the advancement of renewable energy sources. The research project results described above have received funding through the EURIZON project, which is funded by the European Union under grant agreement No.871072.